Polypharmacy among the Elderly - Hosseini, Seyed Reza (J Midlife Health, 2018)
INTRODUCTION: Older people are at risk for polypharmacy due to multiple chronic diseases. Considering the lack of information in this regard, the aim of this study was to investigate the state of polypharmacy among the elderly in the city of Amirkola in northern part of Iran. MATERIALS AND METHODS: This descriptive/analytical cross-sectional study is a part of Amirkola Health and Aging Project that was conducted on 1616 individuals aged 60 years and over. The data about medications were gathered through interviews and observation of prescriptions and medications consumed by patients. The data were analyzed by SPSS software version 18, and P ≤ 0.05 was regarded significant. RESULTS: In this study, 1616 individuals including 883 men (54.6%) and 733 women (45.3%) were investigated. The average age of individuals was 69.37 ± 7.42. Among the investigated individuals, 526 including 368 men (41.7%) and 158 women (21.6%) consumed no medications. The prevalence of polypharmacy in this study was 23.1%, which was 32.7% in women and 15.2% in men (odds ratio = 1.51, 95% confidence interval: 1.10–1.93). The most prevalent group of medications used in both genders was cardiovascular drugs. CONCLUSIONS: Regarding the considerable prevalence of polypharmacy among the elderly, especially in aged women, serious efforts are required to manage polypharmacy. Provision of educational programs for physicians, personnel of pharmacies, and the staff of health-care centers in order for appropriate and safe consumption of medications in aged people is absolutely necessary.